Transcriptome of larvae representing the Rhipicephalus sanguineus complex. (February 2017) - De Marco, Leone; Epis, Sara; Comandatore, Francesco; Porretta, Daniele; Cafarchia, Claudia; Mastrantonio, Valentina; Dantas-Torres, Filipe; Otranto, Domenico; Urbanelli, Sandra; Bandi, Claudio; Sassera, Davide
Abstract: Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae) is possibly the most widespread tick species worldwide, responsible for transmitting several vector-borne pathogens of medical and veterinary importance. Here, we explore the transcriptome of R. sanguineus s.l. larvae (Putignano strain). We sequenced total RNA from R. sanguineus s.l. larvae. A total of 15, 566, 986 short paired-end reads were de novo -assembled into 33, 396 transcripts and then annotated and analyzed. Particular attention was paid to transcripts putatively encoding ATP-binding proteins, due to their importance as mechanisms of detoxification and acaricide resistance. Additionally, microsatellite loci were investigated, as these are useful markers for population genetic studies. The present data and analyses provide a comprehensive transcriptomic resource for R. sanguineus . The results presented here will aid further genetic and genomic studies of this important tick species. Highlights: In depth transcriptomic study of larvae belonging to the tick Rhipicephalus sanguineus . 81 unigenes of the ATP binding cassette family, were described. 1250 transcripts containing microsatellites were detected.